The surface reactivity of iron oxide nanoparticles as a potential hazard for aquatic environments: A study on Daphnia magna adults and embryos - Magro, Massimiliano; De Liguoro, Marco; Franzago, Eleonora; Baratella, Davide; Vianello, Fabio (Scientific reports, 2018)
Nano-ecotoxicology is extensively debated and nanomaterial surface reactivity is an emerging topic. Iron oxide nanoparticles are widely applied, with organic or inorganic coatings for stabilizing their suspensions. Surface active maghemite nanoparticles (SAMNs) are the unique example of naked iron oxide displaying high colloidal and structural stability in water and chemical reactivity. The colloidal behavior of SAMNs was studied as a function of the medium salinity and protocols of acute and chronic toxicity on Daphnia magna were consequently adapted. SAMN distribution into the crustacean, intake/depletion rates and swimming performances were evaluated. No sign of toxicity was detected in two model organisms from the first trophic level (P. subcapitata and L. minor). In D. magna, acute EC50 values of SAMN was assessed, while no sub-lethal effects were observed and the accumulation of SAMNs in the gut appeared as the sole cause of mortality. Fast depuration and absence of delayed effects indicated no retention of SAMNs within the organism. In spite of negligible toxicity on D. magna adults, SAMN surface reactivity was responsible of membrane bursting and lethality on embryos. The present study offers a contribution to the nascent knowledge concerning the impact of nanoparticle surface reactivity on biological interfaces.
Keywords: biotest; Daphnia; embryo nesavčí; analýza přežití; Animals; železité sloučeniny; kovové nanočástice; Embryo, Nonmammalian; lokomoce; Survival Analysis; zvířata; chemické látky znečišťující vodu; Metal Nanoparticles; Locomotion; Ferric Compounds; Biological Assay; Water Pollutants, Chemical